2021
DOI: 10.1186/s12872-021-01987-7
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of coarctation of the aorta with a long and angled isthmus by two- and three-dimensional echocardiography: a case report

Abstract: Background Prenatal diagnosis of coarctation of the aorta (CoA) is challenging for most examiners. The malformation often occurs at the aortic isthmus, which is a short segment between the origin of the left subclavian artery and the insertion of the ductus. We report herein a rare case of CoA with a long, angled, and hypoplastic isthmus. The echocardiographic characteristics and postmortem findings are presented to approach the skill of fetal diagnosis. Case pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Diabetes has been linked to inflammation, activation of the renin-angiotensin-aldosterone system, microvascular dysfunction, and bad insulin signaling in the heart. Also, people with diabetes are more likely to develop type 2 diabetes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes has been linked to inflammation, activation of the renin-angiotensin-aldosterone system, microvascular dysfunction, and bad insulin signaling in the heart. Also, people with diabetes are more likely to develop type 2 diabetes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A new meta-analysis shows that women who develop impaired glucose tolerance during pregnancy are 1.5 times more likely to have a heart attack in the first year after giving birth. This higher risk exists whether or not the woman develops type 2 diabetes after giving birth [ 26 ]. The authors thought that both GDM and PE might make pregnant women more likely to have heart problems after giving birth.…”
Section: Discussionmentioning
confidence: 99%
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
“…For both risk of bias and applicability to the review question, the majority (n=129) had some concerns,41 42 44–67 69–87 89–149 151–170 172–174 and five had a high level of concern43 68 88 150 171 (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…To improve the early diagnosis of CoA, several diagnostic tests have been used in clinical practice. Currently, cardiac ultrasound is a routine test for CoA, and studies to improve the prenatal diagnosis of CoA have recently been conducted based on it (17,18). However, since the aortic coarctation occurs mainly in the isthmus and its physical changes are not clear, it is often examined with the help of CT and MRI.…”
Section: Computed Tomography Angiography and Manual Measurementmentioning
confidence: 99%